LUFFA ACUTANGULA (LINN.) ROXB. VAR. AMARA (ROXB.) A CONSENSUS REVIEW - NIPUN DASHORA; L. S. CHAUHAN; NEERAJ KUMAR (International Journal of Pharma and Bio Sciences, 2013)
Nature has been a source of medicinal agents for thousands of years, herbal medicines which formed the basis of health care throughout the world since the earliest days of mankind are still widely used. Luffa acutangula is widely growing vegetative climber and is used traditionally in folklore medicines for ailments including jaundice, diabetes, liver diseases, skin diseases, wounds etc. Taking into consideration, its medicinal importance and taxonomic confusion, exhaustive study of the morphology, tissue culture, phytochemical constituents, ethnobotany and biological activities of Luffa acutangula var. amara Roxb. fruits is carried out which will provide useful information in regard to its correct identity and help to differentiate from the closely related otherspecies of Luffa.